2016
DOI: 10.18240/ijo.2016.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diaton transpalpebral tonometer with applanation tonometry in keratoconus

Abstract: Measurements obtained using a Diaton tonometer are not affected by corneal biomechanics; however, its poor agreement with Goldmann AT values calls into question the added value of using a Diaton tonometer to measure IOP in keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Such modern devices designed for IOP measurement, and in the future allowing for the analysis of corneal biomechanical parameters are:Diaton: The portable and manual Diaton device does not need sterilization or anesthesia. As the IOP is measured through the eyelid over the sclera, there is no influence of corneal thickness or corneal stiffness [101]. Icare: The advantage of Icare is that it is portable and it does not need sterilization or anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modern devices designed for IOP measurement, and in the future allowing for the analysis of corneal biomechanical parameters are:Diaton: The portable and manual Diaton device does not need sterilization or anesthesia. As the IOP is measured through the eyelid over the sclera, there is no influence of corneal thickness or corneal stiffness [101]. Icare: The advantage of Icare is that it is portable and it does not need sterilization or anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Diaton: The portable and manual Diaton device does not need sterilization or anesthesia. As the IOP is measured through the eyelid over the sclera, there is no influence of corneal thickness or corneal stiffness [101].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, the differences are significant; indeed, it is not possible to relate values obtained with DT to reference values. Other studies reported poor agreement between DT and GAT, 32 under or overestimation of the IOP, 33 and a significant influence of the positioning on the IOP measurement with the DT. 34 A moderate correlation between AT and DT was found when used on a normal eye in a study 35 and when corrected for central corneal thickness in another study.…”
Section: Discussionmentioning
confidence: 90%
“…Особенности течения глаукомы, приводящей к значительной доле инвалидизации среди страдающих этим заболеванием людей, определяют актуальность контроля ВГД автономно от медицинского персонала. При значительном многообразии приборов, с помощью которых можно выполнять измерение офтальмотонуса, в многочисленных исследованиях обсуждается их прецизионность и допустимость использования для персонализированного контроля при различных заболеваниях [6][7][8][9][10][11][12]. Оптимальным вариантом при глаукоме, безусловно, является возможность измерения ВГД в домашних условиях с той частотой, которая необходима при индивидуальном течении заболевания.…”
unclassified